Replacement of soybean meal by conventional and coated urea in dairy cows: intake, digestibility, production and composition of milk - Geógenes da Silva Gonçalves; Marcio dos Santos Pedreira; José Augusto Gomes Azevedo; Antonio Jorge Del Rei; Herymá Giovane Oliveira Silva; Fabiano Ferreira Silva (Acta Scientiarum. Animal Sciences, 2014)
This study evaluated the effect of dairy cows’ diets containing two different sources of urea on dry matter intake, nutrient apparent digestibility, and milk production and composition. Eight crossbred cows (Holandês x Zebu) were confined and randomly assigned to four sequential diets distributed in two 4 x 4 Latin: SM = soybean meal; SRU 0 = conventional urea (CU) 100%/slow release urea (SRU) 0%; SRU 44 = CU 56%/SRU 44%; SRU 88 = CU 12%/SRU 88%. Experimental periods consisted of 21 days, with total duration of 84 days. Dry matter intake, neutral detergent fiber, organic matter, crude protein, and total digestible nutrients were not affected by experimental diets. Dry matter and neutral detergent fiber digestibility coefficient presented average values of 69.43 and 51.07%, respectively. Average digestibility of crude protein was 65.43%. Average milk production was 9.609 kg. The partial replacement of soybean meal by conventional urea and slow release urea, at 2.1% of the diet dry matter, showed that these sources of urea can be offered without production impairment for dairy cows.